THE USE OF “IDENTITY PARADE” GAME AS A STRATEGY TO IMPROVE STUDENTS’ SPEAKING SKILL IN DESCRIBING PEOPLE AT SECOND GRADE STUDENTS OF SMPI HASANUDDIN DAU MALANG - Rizky Fitri Lestari (Journey: Journal of English Language and Pedagogy, 2018)
Speaking is the most fundamental skill in learning language. Unfortunately the researcher found the students’ speaking problem when she conducted preliminary study in SMP Hasanuddin. Therefore, the researcher decided to solve the problem by conducting Classroom Action Research (CAR) using “Identity Parade” game technique. It consists of four steps in 2 cycles, there are: planning of the action, implementing, observing, and reflecting of the action. The subject of this research were 17 students at eighth grade (VIIIB) . The instruments of this research were speaking test, observation check-list and questionnaire. The result of the the speaking test in this study described as; the students who passed the standard score in the preliminary study improved from 43.75% to 71.43% at the cycle 1 and 86.67% at the end of cycle 2. This case shows that there are significant improvement in students’ speaking skill and the learning process was stopped, because the score had met the minimum passing grade which is 75 %. Therefore, “Identity Parade” game had been proved that it could be one of teaching technique to improve the eighth graders’ speaking skill in describing people at SMPI Hasanuddin Dau Malang.